Peran User-Centered Design terhadap Perancangan User Experience Aplikasi Community Marketplace - Yaputra, Mario (JDMIS: Journal of Data Mining and Information Systems, 2023)
Today, User Experience (UX), which is a very important component for interacting in an application, actually brings difficulties to its users. User Experience (UX) has the goal of making it easier for users to solve the problems they want to solve, as well as providing directions and illustrations for users so they don't experience difficulties and misunderstandings when using an application. PT. XYZ is a company engaged in providing community marketplace websites. From the problems faced by the market, the limitations of the platform often make users experience difficulties in communicating, as well as accessing and managing information about the desired activity. Therefore, a prototype design was carried out using a user-centered design approach and usability testing methods with the aim of digging up information about the needs of the users. The usability score and prototype design of the website obtained from the final research results will be used to design a website prototype that can assist users (hosts & guests) in collecting participant data, as well as accessing and managing information of interest until the end of the event. The final results of the research show that the process of designing a website prototype using a user-centered design approach produces a usability score of 93.06 or 95.2% through the usability testing method.